The intersection of welfare stigma, state contexts and health among mothers receiving public assistance benefits - Jessica Lapham; Melissa L. Martinson (Elsevier, 2022)
The stigmatizing nature of the US welfare system is of particular importance not only because it has shown to deter eligible applicants from participating in public assistance programs despite facing economic hardship, but also because stigma is an important fundamental cause of health inequities. Although scholars agree stigma is shaped by individual and contextual dimensions, the role of context is often overlooked. Given the heterogeneous nature of US state welfare environments, it may be critical to consider the ways in which state policy, social and economic contexts condition the relationship between welfare stigma and health. Using a multilevel lens, this study first examined the impact of experienced and perceived welfare stigma on self-reported health among female public assistance recipients with children. Second, we assessed the moderating effect of uneven state TANF policies, income inequality, and negative public welfare attitudes in shaping these associations. Using data from the Fragile Families and Child Wellbeing Study merged with state-level economic and social measures, we employed a series of multilevel logit models with random effects. Findings show experiences and perceptions of welfare stigma are significantly linked to poor health regardless of state contexts, and outcomes vary markedly by race, ethnicity and education. States with strong anti-welfare attitudes amplified the relationship between experienced welfare stigma and poor health for Black and Hispanic mothers, and state economic contexts modified the relationship between experienced welfare stigma and poor health for mothers with less than a high school education. TANF generosity had no moderating effect on health suggesting state policy environments have limited ability to protect welfare recipients against the stigmatizing effects of the US welfare system. Results have implications for explaining stigma related disparities in health within the context of U.S. welfare environments and informing policies that may be key levers for reducing health inequities.